(untitled) (Eurasian Journal of History, Geography and Economics, 2022)
The management of any farm is decided by the staff of the entity. In order to organize this process highly efficiently, it also requires the management of the staff itself. This process is also based on a number of principles, but is done by many methods. issues are discussed.